ENHANCING RECREATIONAL SPORTS EXPERIENCE - I Made Krisna Dinata; I Made Muliarta; Luh Putu Ratna Sundari; Nila Wahyuni (Sport and Fitness Journal, 2023)
Lumintang Field is utilized as a recreational sports facility. An ergonomic assessment is necessary to ensure that individuals can engage in recreational sports activities in a healthy, safe, comfortable, effective, and efficient. The objective of this study is to evaluate the ergonomic aspects of the recreational sports facilities at Lumintang Field. The data collected through observations, measurements, and interviews carried out with users, vendors, and staff members. Lumintang Field offers a sufficient supply of drinking water and a canteen. Recreational sports participants have limited knowledge concerning the appropriate exercise load, which can result in adverse consequences such as sports injuries. Regarding body posture aspects, attention should be given to the compatibility of anthropometric dimensions of gymnastic equipment to ensure safe usage for all age groups. In terms of environmental conditions, Lumintang Field offers a comfortable environment for exercising during the day, with good air circulation and shade provided by trees. Lumintang Field can be used throughout the day, but sports activities tend to be carried out in the morning and evening. Some rule violations were also identified, such as bringing dogs and smoking. The research recommendations include improving the anthropometric dimensions of gymnastic equipment, and enhancing lighting in specific areas. In order to achieve optimal utilization, ergonomic research and practices are highly necessary in the design and maintenance of recreational sports facilities.